2022
DOI: 10.1055/s-0042-1758780
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson's Disease: Risk Factor Modification and Prevention

Abstract: The global burden of Parkinson's disease (PD) has increased from 2.5 to 6.1 million since the 1990s. This is expected to rise as the world population ages and lives longer. With the current consensus on the existence of a prediagnostic phase of PD, which can be divided into a preclinical stage and a prodromal stage, we can better define the risk markers and prodromal markers of PD in the broader context of PD pathogenesis. Here, we review this pathogenetic process, and discuss the evidence behind various herit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 181 publications
0
7
0
Order By: Relevance
“…In recent decades, there has been an increase in the prevalence of neurodegenerative diseases. One such disease is Parkinson’s disease (PD), characterized by progressive degeneration of dopaminergic neurons in the substantia nigra pars compacta (SNpc) [ 30 ]. While some researchers believe that the main factors involved in the development of PD are population aging and genetic mutations, a number of studies have shown that PD can be caused by exposure to certain exogenous toxic substances, which can cause high levels of oxidative stress [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, there has been an increase in the prevalence of neurodegenerative diseases. One such disease is Parkinson’s disease (PD), characterized by progressive degeneration of dopaminergic neurons in the substantia nigra pars compacta (SNpc) [ 30 ]. While some researchers believe that the main factors involved in the development of PD are population aging and genetic mutations, a number of studies have shown that PD can be caused by exposure to certain exogenous toxic substances, which can cause high levels of oxidative stress [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent epidemiological studies have linked environmental factors, including pesticide exposure, to the development of idiopathic Parkinson's disease (PD) (Ball et al 2019;Ng et al 2024; Rajan and Kaas 2022). Rotenone (RTN), a hydrophobic substance derived from Leguminosae plant roots and used as a natural pesticide, readily crosses the blood-brain barrier (BBB) and strongly inhibits mitochondrial complex I in the electron transport chain (Ibarra-Gutiérrez et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…According to the epidemiological studies, the prevalence of PD increases with the rise of aging populations. The incidence of PD is 1.5–2% among people over 60 years old and up to 4% in people over 80 years old ( Marino et al, 2020 ), and the global PD patients has increased from 2.5 to 6.1 million since the 1990s ( Rajan and Kaas, 2022 ). In China, the prevalence of PD was 1.37% in people over 60 years old, and the number of people suffering from the disease has exceeded 3.62 million indicated by a community-based study ( Qi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have found that dyssomnia, sleep disorder, mental disorder, cognitive disorder, and somatoform autonomic dysfunction are commonly exist in PD patients and occur among different stages of motor symptoms, affecting the life quality of patients ( Suzuki et al, 2022 ). Due to the high rate of disability and a long therapeutic procedure, PD brings heavy burden and troubles to patients and their families ( Zhang et al, 2005 ; Kumar et al, 2010 ; Seol, 2010 ; Rajan and Kaas, 2022 ). Therefore, it is extremely important to study the etiology and pathogenesis of PD nowadays.…”
Section: Introductionmentioning
confidence: 99%